MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA PAMIJAHAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Nurhasan, Abdul Khodir; Sakilah , Ilah (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
Implementation of community service in Pamijahan Village, Pamijahan District, Bogor Regency, West Java. The potential of Pamijahan Village is very abundant, such as in the fields of agriculture, plantations and there are tourism that need to be developed, so the need for qualified Human Resources (HR) so that there is an understanding in managing and developing the potential of Pamijahan Village. then the purpose of this community service activity is to help the public get to know Islamic banks. Community service that begins with observations of local villages to find out and understand their potential. Then do the planning, implementation and evaluation. The results of this observation show that there is a lot of potential, and the majority of Pamijahan Village residents do not know more about Islamic banks, with not many Islamic bank users. The method used is socialization. the result of this socialization activity is to help the community in getting to know Islamic banks and to motivate people to use Islamic banks.